Making of the Self through Spiritual Striving and Material Quest in the Pursuit of Happyness - GC, Saroj (Literary Studies, 2023)
This Paper examines how the protagonist, Chris Gardner, an African American, in Gabriele Muccino's film the Pursuit of Happyness grapples with underlying identity crisis in first decade of 21st century while pursuing his happiness. The film nowhere claims that the color of skin is an operative social component that is detrimental to pursuit of dream, the American Dream. However, the amnesiac picture of racial history is undercut by the choice of protagonist, Chris Gardner, an African American makes and grapples to accomplish it. In the light of this situation, the paper tries to tests one of the important notions of critical race theory, double consciousness, a putatively collective African American socio-historical conditions as characterized and postulated by Du Bois, and explore the dilemma inherent in Chris Gardner's pursuit of happiness. More significantly, the paper analyzes the liminal space the protagonist lives, experiences, undergoes and wrestles, and tries to come out of it if possible. Pointedly, it traces the protagonist's spiritual striving to the past, and explores the material need of the present. The paper concludes that how his dream has been subject to racialized ascription, and how and what the dream means for Chris Gardner. The paper clearly demonstrates the philosophical shift— the spiritual striving to the material quest in Gardner's pursuit of the dream.